Destruction of chlorinated pesticides in TiO2-enhanced photochemical process - Adriana Zaleska; Jan Hupka; Andrzej Silowiecki; Marek Wiergowski; Marek Biziuk (International Journal of Photoenergy)
Aqueous solutions containing 200mg/dm3 of lindane, p,p´-DDT and methoxychlor were photodegraded for 60 min in UV/TiO2/O2 system. Sparged air was introduced into the reactor environment. Titanium dioxide supported on glass, hollow microsphers served as the photocatalyst. Pesticides destruction ratio was evaluated and oxidation products were identificated by gas chromatography with thermionic specific detector (GC-TSD) and mass spectroscopy detector (GC-MS). The concentration of pesticides after reaction was determined in the liquid phase, in the solid phase (adsorbed on the photocatalyst) and in the gas phase. The experimental data indicates that pesticide removal with the gas phase was insignificant, therefore it was neglected in the assessment of the photodegradation efficiency. From 14% to 58% of investigated pesticides remained adsorbed on catalyst surface after photodegradation. High content of pesticides in the solid phase after reaction resulted from their low solubility in water and indicates significant adsorption ability of the pesticides by TiO2.